THE FRAGILE MASCULINE: GENDER, SEXUALITY, RACE AND RELIGION AS A COMPLEXITY OF ELISCHA'S CHARACTER IN “LOVE ME HARDER” BY CHICKS* (2020) - Maisaroh, Umi (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2022)
Performance elements such as stage properties, actors, text, music, lighting, and other elements appear when the performance represents symbols and meanings. This study tries to deconstruct ideas about gender and sex through an exploration of reading the meaning of the elements of the 'Love Me Harder' performance by the theatre group CHICKS*. The performance was held at the LOFFT Leipzig Theater in February 2020. The data collected was from watching the performance booklet and the theatre group's website. As a theoretical framework, this research will use literature studies, for example, theorists Susan Bordo (2000), Judith Butler (1999), Daniel Boyarin (2003), and Ann Stoler (1996). This study presents the discourse on the meaning of the body and the type or form of sex, especially the phallus, as something that carries feminine or masculine traits naturally or culturally. From the analysis, it can also be explained that the show tries to dismantle the stereotypes attached to masculine traits and criticizes masculine domination and patriarchy concerning power and colonialism, and discrimination against race and religion.Keynotes: performance, Love Me Harder, CHIKS*, stereotype